Operational short–range analytical air pollution modelling. (4th August 2014) - Tirabassi, T.; Rizza, U.
Operational models that use solutions of the advection–diffusion equation based on more realistic assumptions than that of homogeneous wind and eddy diffusivity coefficients are presented. In particular, these solutions accept that wind and eddy diffusivity profiles are power functions of the height. Moreover, a practical short–range model evaluating ground–level concentrations from elevated sources, which utilises a Fickian–type formula in which the source height is a simple function of the wind velocity and eddy diffusivity profiles, is presented.